APPLICATION OF GEOGRAPHIC INFORMATION SYSTEM (GIS) TO SOLID MINERAL RESOURCES INFORMATION MANAGEMENT - Opafunso, Z O; Ajaka, E O (Biological Sciences - PJSIR, 2004)
In this paper, a typical GIS information retrieval model for topographical, geological, minerals and land use maps developed. A 5-layer data topographical and geological information modelling and retrieval for a typical mineral region (Niger Delta, Nigeria) was also designed, for the use of government agencies and prospective investors. We also examined how GIS can be used to select reclamation plan options; from land use and land cover maps.